Psychological diagnosis of terrorist thought among youth - Al Subaihi, Ali bin Ahmed; Bekai, Haifa Tayseer (Journal of Educational and Psychological Sciences, 2018)
Arab and non-Arab societies suffer from the pain of terrorism that has gripped all aspects of life, and the suffering of societies has reached a point where they have mobilized all their energies and their material and human resources to combat it. And the contribution of researchers to support efforts to combat terrorism scientifically, legitimately to find the psychological model of the terrorist industry, and the behavioral list that shows the psychological transformation of the terrorist at each stage of the model through the use of qualitative approach to the analysis of the traditional theoretical framework in the study of violence in general and terrorism in particular, Interviews of a sample of the parties to the terrorist operation. The research concludes that the terrorist industry starts from the point of feeding the intellectual conflict related to the young man geographically or culturally to reach the hostility of the local community to the young man or society that is causally related to the intellectual conflict by passing through the amplification point, which finally takes the young man to the turning point where the young man becomes hostile to his society And is psychologically ready to carry out terrorist behavior. The research used this psychological model to develop a list of behaviors that in general (or mostly) reflect the psychological state of a person suffering from personal disorders at every point in the terrorist industry. This research is a continuation of previous scientific efforts in the field of counterterrorism; With its diagnostic focus based on the psychological angle in its interpretation and construction. The study concludes with the recommendation that behavioral changes should be observed on young people (with their different intellectual orientations, levels of religiosity and adherence to the values ​​and systems of society) that lead to disunity with the family, a problem with authority, social intransigence, social isolation or self-isolation.
Keywords: psychiatric diagnosis; youth; terrorism; societal hostility; personality disorder